Dynamics of Childless Marriage Through the Lens of Maqasid Al-Shari’a - Rasyid, Arbanur; Jarudin, Jarudin; Saleh, Idris; Lubis, Rayendriani Fahmei (Jurnal Ilmiah Peuradeun, 2024)
There is a trend among Muslims, especially married couples, not to or delay having children. Meanwhile, having children horizontally is one of the main goals of marriage to continue the human race. This literature research used secondary data which were collected in two ways: manually and online. Manual data comprised information derived from major books on marriage, maqasid al-shari’a, and others. Online data were acquired in the form of articles attributed to research themes using an open journal system. The collected data were subsequently analyzed through data reduction, data display, and verification techniques. This research found that the goal of marriage in Islamic law referred to both horizontal and vertical aspects. Vertically, marriage aimed to display one’s level of allegiance to God, who created him. This obedience was accompanied by a faith test in the shape of the ability to restrict and control desires in the face of the magnitude of human sexuality’s challenges and God’s call to produce pious offspring. Horizontally, the aim of marriage was directly tied to oneself, others, and the surrounding environment. Marriage, in this perspective, served a social function by creating a communal family. Families could be formed and developed when there were children and offspring. As a result, the presence of children in a marriage is essential for establishing society, nation, and civilization, because those all cannot exist without children.